2011
DOI: 10.1590/s0100-06832011000500008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física de três solos sob colheita mecanizada de cana-de-açúcar

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
2
22
0
8
Order By: Relevance
“…Thus, the increased penetration resistance at the surface reduced macroporosity and increase the proportion of micropores. In sugarcane cultivation, soil disturbance occurs at crop replanting, usually every five years, so that the traffic effect is accumulated mainly at the surface (Cavalieri et al, 2011). It is noteworthy that, in the traffic control, the soil remains compacted by machinery in the crop inter-row center, which does not limit the root growth (Otto et al, 2009) and can increase the longevity of sugarcane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increased penetration resistance at the surface reduced macroporosity and increase the proportion of micropores. In sugarcane cultivation, soil disturbance occurs at crop replanting, usually every five years, so that the traffic effect is accumulated mainly at the surface (Cavalieri et al, 2011). It is noteworthy that, in the traffic control, the soil remains compacted by machinery in the crop inter-row center, which does not limit the root growth (Otto et al, 2009) and can increase the longevity of sugarcane.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown the effect of compaction on the soil physical quality, increasing soil density and mechanical strength (Materechera, 2009;Cavalieri et al, 2011) and decreasing the pore volume, particularly of macropores (Streck et al, 2004;Souza et al, 2006;Braunack & McGarry, 2006). Soil compaction also affects the soil structure, changing the aggregate stability and modifying the particle arrangement (Tullberg et al, 2007;Roque et al, 2010;Vezzani & Mielniczuk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The LLWR concept is increasingly applied to sugarcane cultivation, and recent studies that modeled soil compaction in cane fields have helped to minimize the impacts of compaction on the structure of soils planted to sugarcane (Severiano et al, 2009;Silva et al, 2009;Cavalieri et al, 2011;Roque et al, 2011). However, there has been little study of the effects of soil structural degradation on the yield and quality for industrial processing of subsequent crops as well as its effect on the growth of sugarcane cultivars with different maturation cycles.…”
Section: Introductionmentioning
confidence: 99%
“…These two examples corroborate the observation about "individual soils" by Dexter (2004a) and show that S is not an absolute indicator of soil physical quality. It is, therefore, questionable whether anything can be inferred based on the value of S alone, even if this is common practice in many publications (Calonego & Rosolem, 2011;Cavalieri et al, 2011) Evaluation of soil quality depends on understanding the insertion of soil in the landscape-soil-plantatmosphere system; therefore, it depends on knowledge of how the system functions and the underlying physical, chemical and biological processes. We mentioned in the Introduction that process-based models capable of simulating these processes applied to agronomy, hydrology, ecology and meteorology are being developed by specific research groups and are available to the scientific community.…”
Section: S Versus Relative Densitymentioning
confidence: 99%